Choline Chloride: Urea-based deep eutectic solvent as additive to proton conducting chitosan films - Wong, W. Y.; Wong, C. Y.; Walvekar, Rashmi; Khalid, Mohammad * (School of Engineering, Taylor's University, 2018)
Chitosan (CS) film has been regarded as one of the bioresources that shows its ability to conduct proton upon modification. Nonetheless, CS film in nature is brittle and shows extremely high swelling degree towards water, leading to the impractical applications for fuel cell membranes and batteries. Formation of natural polymeric film requires plasticiser to crosslink natural polymers in improving the mechanical strength. Here, we investigate the potential of choline chloride (ChCl) and urea based deep eutectic solvent (DES) as additive in CS film with the aim to improve the mechanical property of the film. In this study, ChCl:urea- based DES was mixed with pure CS solution at different volume ratio and casted into a film. The film will be investigated on the functional groups, water uptake, ionic conductivity, proton exchange capacity and its morphology. Based on the SEM morphology result, it was found that addition of DES improves the homogeneity of the membrane film mainly attributed to the presence of strong bonds between the CS monosaccharides. Besides that, it also contributed towards better plasticising effect of the film that improves the flexibility of the membrane. The addition of DES has further improved the ionic conductivity of CS film from 2.98×10-3 to 1.23×10-2 S/cm; while drastically reduced the water uptake from 698.89 % to 180.67 %.